Autoxidation as a trigger for the slow release of volatile perfumery chemicals. (9th June 2014) - Indradas, Brinda; Hansen, Christopher; Palmer, Michael; Womack, Gary B.
ABSTRACT Finding suitable precursor molecules that extend the lifetime of perfumes by decomposing and releasing fragrant chemicals under relatively mild, ambient conditions remains a significant challenge. Although the majority of effort in this regard has been directed toward using hydrolysis reactions as the release event, autoxidation and subsequent fragmentation reactions also would appear to be well suited for this purpose given the constant exposure of deposited perfumes to atmospheric oxygen. Divinyl ethers, prepared from enolizable perfume aldehydes, have two olefin functions adjacent to the ether oxygen and were found to provide prolonged release of fragrant carbonyl compounds by an autoxidative fragmentation process. After deposition onto cotton terry cloth from a liquid fabric softener, dynamic headspace analysis showed the liberation of the parent aldehyde along with a one‐carbon smaller carbonyl compound and the enol formate ester of the parent aldehyde. Depending on the structure of the divinyl ether both liberated carbonyl compounds can be perfumery materials and both always were released from the cotton at significantly higher levels than the unmodified parent aldehydes used to prepare reference samples. Autoxidation of the divinyl ethers initiated by peroxy‐radical addition to alkene functions would account for the oxidative cleavage reactions yielding the smaller carbonyl compounds and the enol formates. Hydrolysis of the enol formate could generate the parent aldehyde. The liberation of volatile carbonyl compounds from divinyl ethers demonstrates the potential usefulness of autoxidation as a trigger for the sustained release of fragrant compounds from suitably designed precursors. Copyright © 2014 John Wiley & Sons, Ltd.